1983
DOI: 10.1111/j.1365-2621.1983.tb14810.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Properties of Pork as Affected by Electrical Stimulation, Post‐Slaughter Chilling and Muscle Group

Abstract: Left sides of 30 slaughtered pigs were electrically stimulated (ES); right aides were not stimulated (NES). Sides were placed in a conventional cooler (24 hr) or blast freezer (3 hr) or showered with a brine solution (15.8% salt, -5.6"C for 3 hr). Twenty-four hr postmortem, picnic shoulders were removed, dissected into four muscle groups and determinations made for certain processing properties. ES decreased (P < 0.05) pH values for predominantly white muscles, increased (P < 0.05) juice loss during cooking fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Based on these results, we concluded that the best combination of assay conditions for extraction of salt soluble protein of beef and pork muscle included pH 6.0, extraction volume 15 X sample weight, centrifugation force 4000 x g and homogenization time 90-120 set (Table 5). Using this combination of assay conditions resulted in higher yields of SSP from pork LD and beef LD and SM muscles than most previous studies including some using chicken (Saffle and Galbreath, 1964;Hudspeth and May, 1967;Maurer et al, 1969;Acton, 1972a,b;Anderson and Gillett, 1974;Swasdee et al, 1983;Turgut, 1984) except those with buffers containing phosphate (Bernthal et al, 1991).…”
Section: Resultsmentioning
confidence: 76%
“…Based on these results, we concluded that the best combination of assay conditions for extraction of salt soluble protein of beef and pork muscle included pH 6.0, extraction volume 15 X sample weight, centrifugation force 4000 x g and homogenization time 90-120 set (Table 5). Using this combination of assay conditions resulted in higher yields of SSP from pork LD and beef LD and SM muscles than most previous studies including some using chicken (Saffle and Galbreath, 1964;Hudspeth and May, 1967;Maurer et al, 1969;Acton, 1972a,b;Anderson and Gillett, 1974;Swasdee et al, 1983;Turgut, 1984) except those with buffers containing phosphate (Bernthal et al, 1991).…”
Section: Resultsmentioning
confidence: 76%